PELAKSANAAN LAYANAN INFORMASI DITINJAU DARI MODEL CONTEXT INPUT PROCES PRODUCT (CIPP) - Tri Cahyono; Desika Lumba; Emma Juwita M Sirait (Cendekia Sinergi Akademika, 2025)
Information services aim to equip students with knowledge and understanding of guidance and helpful counseling for selfknowledge, planning and developing their lives as students, family and community members. The research discussed how implementing information services in schools was viewed from the CIPP model. The study used descriptive qualitative methods, and the data analysis techniques used in this research were data reduction, presentation, data and conclusions. Input preparations made by BK teachers before implementing services include distributing AKPD, compiling RPL, and providing media and techniques/methods. Process information services were carried out through classical guidance, guidance boards and social media. Product evaluation was carried out in several ways, including questions that were asked directly and randomly appointed. Then, students provided conclusions on sheets of paper and, finally, through the quiz application. From the evaluation results, students can understand the material well, and if the counseling teacher randomly appoints them, students can explain according to their understanding